Peptides derived from the gastrointestinal digestion of amaranth 11S globulin: Structure and antioxidant functionality - García Fillería, Susan Fiorella (2021)
The relationship between structural and physicochemical properties and antioxidant activity of peptides from amaranth 11S-globulin was studied. Peptides AWEEREQGSR, TEVWDSNEQ, IYIEQGNGITGM and YLAGKPQQEH had the greatest in vitro activity (ORAC, HORAC). GDRFQDQHQ, HVIKPPSRA and KFNRPETT were the most active ones against Cu+2 /H2O2-induced-LDL oxidation. In a cellular system (H2O2-induced-Caco2-TC7), TEVWDSNEQ, IYIEQGNGITGM, GDRFQDQHQ, LAGKPQQEHSGEHQ and KFNRPETT were the most effective in decreasing ROS, while the effects on SOD, GPx, and GSH were variable. To understand the structure–antioxidant activity relationships, the content of aromatic and acidic amino acids, the degree of hydrophobicity and the charge distribution on the accessible surface of peptides structures obtained by molecular dynamics were analysed. The low correlation between in vitro, ex vivo and cellular activities could be explained by the influence of physicochemical and structural properties on the interaction with complex systems (LDL/cells), peptide modifications and/or mechanisms other than direct ROS inhibition in the cells.